2013
DOI: 10.1097/wnr.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

The upper brachial plexus defect model in rhesus monkeys

Abstract: To establish a model for nerve grafts and determine the anatomic characteristics of the brachial plexus in rhesus monkeys. Ten specimens of the brachial plexus were obtained from five rhesus monkey cadavers. Anatomic dissection of the brachial plexus was systemically performed. The length of each root, trunk, and each division was measured using a Vernier caliper proximodistally. The anatomic distributions of the suprascapular, axillary, and musculocutaneous nerve were documented. The brachial plexus of rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Studies involving the anatomy of the brachial plexus and its applications in experimental models have been proposed and carried out in rats, dogs, cats, rabbits and other species (Getty 1986;Anson et al 2013;Bobkiewicz et al 2016). However, Lu et al (2013) reported that non-human primates are considered more adequate experimental models for training and development of new techniques and materials for humans due to the anatomic similarity of their brachial plexuses and mode of locomotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies involving the anatomy of the brachial plexus and its applications in experimental models have been proposed and carried out in rats, dogs, cats, rabbits and other species (Getty 1986;Anson et al 2013;Bobkiewicz et al 2016). However, Lu et al (2013) reported that non-human primates are considered more adequate experimental models for training and development of new techniques and materials for humans due to the anatomic similarity of their brachial plexuses and mode of locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors emphasised comparative anatomy aspects (Kanagasuntheram & Mahran 1960;Mizuno 1969;Booth et al 1997;Ribeiro et al 2005;Cruz & Adami 2010;Araújo et al 2012). Even when an experimental model approach was considered (Lu et al 2013), peripheral nerves as well as their frequency and the muscles that were innervated by them were not completely recorded. This kind of information is important when new approaches and techniques involving thoracic limbs are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 10 dissected plexuses, all presented their origin in the ventral branches of C5 to T1, although in one animal there was a delicate contribution of C4, and in another one there was a delicate contribution of T2. The origin of the plexus between C5 and T1 is very nearly a rule for primates, having been reported in G. senegalensis (Kanagasuntheram & Mahran 1960), S. sciureus (Mizuno 1969), P. ursinus (Booth et al 1997 (Lu et al 2013;Santos-Sousa et al 2016) and human beings (Parada et al 1989;Zhang et al 2016). However, intraspecific variations concerning the spinal segments of origin are also reported in those studies that used more specimens, as in the case of C. apella (Ribeiro et al 2005) and M. mulatta (Santos-Sousa et al 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Galago senegalensis senegalensis (Kanagasuntheram & Mahran 1960); Saimiri sciureus (Mizuno 1969;Araújo et al 2012); Cercopithecus pygerythrus (Booth 1991); Papio ursinus (Booth et al 1997); Cebus apella (Ribeiro et al 2005); Lagothrix lagothricha (Robertson 1944;Cruz & Adami 2010); Pan paniscus (Kikuchi et al 2011); Macaca mulatta (Lu at al. 2013;Santos-Sousa et al 2016); and Callithrix jacchus and Callithrix penicillata .…”
Section: Introductionmentioning
confidence: 99%